IL-18 and IL-12 induce intestinal inflammation and fatty liver in mice in an IFN-γ dependent manner. Issue 6 (1st December 2000) - Chikano, S; Sawada, K; Shimoyama, T; Kashiwamura, S-I; Sugihara, A; Sekikawa, K; Terada, N; Nakanishi, K; Okamura, H
Abstract : BACKGROUND: In murine models of inflammatory bowel disease, colonic inflammation is considered to be caused by an aberrant Th1-type immune response. AIM: To investigate if systemic administration of interleukin (IL)-12 and IL-18 to wild-type BALB/c mice induces liver injury and intestinal inflammation, and if pathological changes are observed, what cytokines are involved. METHODS: Mice (BALB/c-wild-type (wt), MRL-lpr/lpr, BALB/c-interferon γ knock out (IFN-γ KO), C57BL/6-inducible nitric oxide synthase (iNOS) KO, and BALB/c tumour necrosis factor α (TNF-α) KO) were injected intraperitoneally each day with IL-12 (20 ng/g/mouse) and/or IL-18 (200 ng/g/mouse). RESULTS: Administration of IL-12 and IL-18 to BALB/c-wt mice induced prominent intestinal mucosal inflammation and fatty liver, leading to piloerection, bloody diarrhoea, and weight loss. IL-12 and IL-18 induced striking elevations in serum levels of IFN-γ that caused NO production, although increased NO had no exacerbating effect on mice. Moreover, iNOS KO mice, or MRL lpr/lpr mice lacking functional Fas were equally susceptible to IL-12 and IL-18. Administration of IL-12 and IL-18 did not induce TNF-α production in wild-type mice, and the same treatment to TNF-α KO mice induced intestinal mucosal inflammation. Furthermore, they had diffuse and dense infiltration of small fat droplets in their hepatocytes associated with an increase in serum levels of liver enzymes. In contrast, the same treatment in IFN-γ KO BALB/c mice and iNOS KO mice did not induce these changes. CONCLUSIONS: Our study strongly indicates that IL-18 together with IL-12 induces intestinal mucosal inflammation in an IFN-γ dependent but TNF-α, NO, and Fas ligand independent manner, and fatty liver is dependent on IFN-γ and NO.